La valoración de inventarios y su importancia en el patrimonio para la toma de decisiones - Ojeda Jumbo, María Alexandra (2015)
The particular work is directly to the correct valuation of the inventory and the importance of the assets when making decisions for the benefit of the “Calva Business”, which has the goal of establishing accounting procedures base don the application of the current norms, specifically the INTERNATIONAL FINANCIAL REPORTING STANDARD FOR SMALL AND MEDIUM-SIZED ENTERPRISES (IFRS for SMES), which clearly indicate the valuation methods accepted by those bodies that have created of the general instructions at world level, the intention is that this information can be easily compared with any other trading organization in the Word and which business organization in the world and that has similar characteristics of intervention in the market. This methodological research is based on the quantitative focus which is not experimental, making use of descriptive desing and the utilizing methods and techniques in order to gather the most optimum information. Through this process it is intended to make it clear the importance of properly and prudently valuating the inventory, as any correct calculation impacts directly on the assets of the company, due to the fact that it afeccts the profits and results in obtaining the gross profits in sales which is nurtured by the costs incurred in its acquisition. Finally, procedures and improvement strategies are offered which should be adopted by the owner of the company, due to the fact that they are elaborated for the purpose of helping to overcome internal weaknesses and above all, be protected from external threats which could impact on the company´s economy or liquidity.Therefore, it is concluded that the inventory control is essential in all organizations that depend on this sector for economic returns, while it is recommended that a prior, concurrent and subsequent control of goods to ensure their efficient management and accounting record.